A educação para o trabalho na perspectiva dos agentes comunitários de saúde - Donaduzzi, Daiany Saldanha da Silveira (2012)
This is a qualitative, exploratory and descriptive research which aims to understand the education process at work into the perspective of Community Health Agents (CHA). The subjects of this study worked in teams of the Family Health Strategy (FHS) and of Community Health Workers (CHW), involving during the research a total of 25 subjects. Two instruments of data collection were selected: self-administered structured survey questionnaire of socio-demographic data and set of interviews with questions for the technique of focal group. Regarding to socio-demographic data a descriptive statistics was employed; qualitative data collected from the focal groups were analyzed according to Bardin. This study followed the 196/96 resolution of the National Health Council. From the results, majority were female, mean age of 38 years, high school complete and working time between 06 and 10 years. Most of them reported as motivation to join CHA the professional stability, and in their majority they worked as saleswomen before became CHA. The CHA identified that education at work happened in the form of capacitation. Regarding the organizational aspects, capabilities were developed from a already set schedule; without periodicity, with insufficient workload for learning; there were professional privilege in certain areas, related to the access to educational activities after the initial training; there was failure in the way of training disclosure , the physical space where these skills are developed was inadequate, with high number of participants which contributed to the ineffectiveness of audiovisual resources, and community workers did not receive transport assistance for the participation during the training time. Relative to the theoretical and methodological aspects of the training, it was found that the subjects were developed in a superficial condition, with an appreciation of technical terms; issues were directed to the CHA of urban area; There was a lack of space for discussion and exchange of experiences; divergences between theory and practice; similar approaches were applied to different realities of FHS and CHW; the dynamics proposed were interesting; however the case studies did not bring to the group the results reached, and there was not a method to assess the knowledge acquired. Standing out yet in this study, for the CHA, that the capacitation did not contribute significantly to the orientation of the work process, leading them to looking for other strategies, which may assist in their learning. Therefore, creation of collective educational spaces for the CHA are recommended, aiming the transformation of professional practice through the reflexive processes, discussion of proposals and exchanges of experiences, according to the reality and needs of the workers as active subjects in the learning process. Keywords: Community Health Agent; Education; Nursing